Afecciones del confluente íleo-ceco-apendicular en el niño: Round table XXVII Uruguayan Congress of Surgery: coordinator César Arruti - Arruti, César; Lattaro, Díver A; Chavarría, Oscar; Wettstein, Juana; Cabrera Roca de Aguirre, María Teresa; Falco de Torres, Eddita; Rosa, Folco; Sbárbaro, Orestes; Lizaso, Isabel; Pérez Scremini, Alberto (Cirugía del Uruguay, 1977)
This table will deal with the most frequent affections of the ileoceco-appendicular confluent, highlighting those that have special characteristics during childhood and leaving aside those that, · such as traumatic ones, · offer the same characteristics as adults and require the same therapeutic gestures.